Profile of Breastfeeding Practice among Mothers of Brazilian Children Attended in a Dentistry Preventive Program - Chrisostomo, Daniela Alvim [UNESP]; Cunha, Robson Frederico [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: To evaluate the breastfeeding practice of mothers of children assisted in the educational and preventive dentistry program to create actions to promote, protect and support breastfeeding. Material and Methods: This is a cross-sectional study with a quantitative approach carried out in a dental clinic for babies. A questionnaire was applied to the mothers containing 10 multiple choice questions about breastfeeding practices and attitudes. Data were stored in a Microsoft Excel database for descriptive statistical analysis. Results: 614 mothers answered the questionnaire. It was found that 96.4% of mothers considered breastfeeding the best way to feed a baby and the child's health benefits stood out as the main reason (98.7%) for breastfeeding. According to 82.9% of mothers, the ideal time to breastfeed the baby is up to 2 years of age; 81.8% breastfed or intended to breastfeed their children up to this age, finding it perfectly natural to breastfeed in public (72.1%). The greatest fear of mothers was not being able to breastfeed their child long enough (61.4%), feeling guilty about it (77%). On the other hand, breastfeeding in public was considered a fantastic attitude (56.8%). Conclusion: Mothers in this sample have information about the recommendations of the health agencies regarding breastfeeding; however, there was a large weaning index among them.
Keywords: Age Groups; Breast Feeding; Infant Nutritional Physiological Phenomena